The effect of inflammation on the central 5-HT system in mood disorders - Couch, Y (2012)
Inflammation appears to play a major role in the pathogenesis of Major Depression, and understanding the relationship between the immune system and mood disorders is a growing area of research. Patients undergoing cytokine therapy frequently develop depressive-like signs which cease upon termination of treatment. In addition, depressed patients often present with high levels of circulating pro-inflammatory cytokines. There are also significant behavioural correlates between inflammation-associated sickness behaviours and Major Depression, suggesting there is a bidirectional relationship between the immune system and central systems regulating behaviour. Both sickness behaviours in animals and cytokine-induced depression in humans can be reversed with antidepressants targeting the serotonergic (5-HT) system. Against this background, this thesis sought to investigate the role of inflammation in the development of certain specific characteristics of depressive-like states in animal models. Specifically, a single systemic endotoxin challenge (LPS) was used to model acute sickness behaviour and to study the behaviour and molecular effects of this challenge on the 5-HT system. These studies indicated that a single systemic challenge changed the function of the 5-HT system, as well as increasing expression levels of a number of 5-HT-related genes, and markers of inflammation in the CNS. A rodent chronic stress paradigm was employed to investigate whether these changes also occur in animals displaying depressive-like signs. Chronically stressed mice were shown to display significant features of rodent depression; decreased sucrose preference and increased forced swim immobility. These changes were also accompanied by increased expression of 5-HT-related genes and inflammatory markers within the CNS. Importantly, many of the molecular changes observed in LPS-induced sickness behaviour were conserved in the model of stress-induced Major Depression. In particular, increased TNF expression within the CNS was highlighted as a feature in both models. Novel anti-inflammatory agents were used to study the role of TNF in the development of sickness behaviours. Anti-TNF therapy, specifically the fusion protein etanercept, ameliorated sickness behaviour induced by LPS. Together, these data demonstrate that inflammation is capable of significantly changing the 5-HT system, and that stress per se is capable of inducing an inflammatory state within the CNS, which support the thesis that sickness and Major Depression are closely related at a molecular level.